differentiate 4x^3 + 3x^2 -5x +1

when differentiating, we multiply the power by the coefficient and then take the power away by 1 so : y= 4x^3 + 3x^2 -5x +1 then 4 x 3= 12 and 3-1 = 2 meaning the solution is 12x^2. 2 x 3 = 6 and 2-1 = 1 giving a solution of 6x. 1x.-5= -5 amd 1-1= 0 so the x value dissapears as x^0 = 1 and finally the 1 does not have a variable so it can't be differentiated so it is excluded. so dy/dx= 12x^2 + 6x -5 

Answered by James R. Maths tutor

3811 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Express 2(x-1)/(x^2-2x-3) - 1/(x-3) as a fraction in its simplest form.


The polynomial p(x) is, p(x)= x3-5x2-8x+48.Use the Factor Theorem to show that (x + 3)is a factor of p(X)


How do i solve differential equations?


Suppose a population of size x experiences growth at a rate of dx/dt = kx where t is time measured in minutes and k is a constant. At t=0, x=xo. If the population doubles in 5 minutes, how much longer does it take for the population to reach triple of Xo.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences